Effects of Nutrient Levels on Microbial Diversity in Sediments of a Eutrophic Shallow Lake - Zhu, Weitang; Liu, Jing; Li, Qihui; Gu, Peng; Gu, Xiaohui; Wu, Lingling; Gao, Yang; Shan, Jun; Zheng, Zheng; Zhang, Weizhen (Frontiers in Ecology and Evolution, 2022)
Microorganisms can indicate both the water quality characteristics and the health of aquatic environment. Microorganisms have an important influence on the cycling of organic carbon, nitrogen and phosphorus in nature. In this study, we took Taihu Lake, a typical eutrophic lake in China, as the research object, and monitored the northern (Changzhou City) and southern (Changxing County) regions of Taihu Lake for three consecutive years, respectively, and analyzed the microbial diversity in sediments, and then summarized the effects of different nutrient environments on microorganisms in the water column. The results showed that the pollution level in the northern part of Taihu Lake was higher than that in the southern region, where the pollution was mainly in summer (June-July). The pollution in the southern region of Taihu Lake is relatively stable between 2019-2021; the changes in the northern part of Taihu Lake are relatively significant. Microbial diversity in the study area was negatively correlated with the degree of eutrophication of water bodies; microbial abundance was positively correlated with nutrient levels. The functional difference analysis indicated that the microorganisms in the sediments of Taihu Lake in the study area were involved in the nutrient transport and transformation, and played an important role in the purification of the lake water body. This study reveals the relationship between water eutrophication and microbial diversity, and then provides a theoretical basis for the management of eutrophic lakes.